Methodology to determine the probalistic demand of mass attraction centers based on the classification within the framework of macrosystems theory - I. E. Agureev; G. E. Pyshnaya; V. A. Pyshnyi (Вестник СибАДИ, 2022)
Introduction. The calculation of correspondence was described at the beginning of the 20 century in the form of a gravitational model and is based on analogy with the law of universal gravitation. The development of this model can be called J. Wilson’s approach, in which correspondence calculations are performed using an entropy model. The entropy approach operates with various expressions for the entropy of a macroscopic system. At the same time, its equilibrium is achieved at the maximum value of the selected entropy function. The purpose of this work is to develop a methodology for determining the probabilistic demand of mass attraction centers - Shopping centers and to demonstrate the results of its application on the example of shopping centers located on the territory of the city of Tula. Probabilistic demand is necessary to obtain the so-called ‘a priori probabilities’ in the expression of the entropy of the transport macrosystem.Methods and Materials. For the development of the methodology, as well as its further use, the most convenient and promising scientific platform is the theory of transport macrosystems, which is a special case of the general theory of macrosystems. Developed in the works of mainly domestic scientists, it allows you to perform various tasks specific to transport systems.Conclusions. The method of determining the probabilistic demand of the mass attraction centers -Shopping centers, which consists in obtaining a priori probabilities of being in them and their capacities for solving problems of finding equilibrium distributions of visitors, was developed with the aim of further developing the macroscopic approach in the study of Shopping centers. The main purpose of the technique is to use the results obtained in solving problems about the equilibrium states of the drains of transport and the road network in the framework of the theory of transport macrosystems.